2009
DOI: 10.3171/2008.5.17558
|View full text |Cite
|
Sign up to set email alerts
|

Predicting aneurysm rupture probabilities through the application of a computed tomography angiography–derived binary logistic regression model

Abstract: Object. The goal of this study was to establish a biomathematical model to accurately predict the probability of aneurysm rupture. Biomathematical models incorporate various physical and dynamic phenomena that provide insight into why certain aneurysms grow or rupture. Prior studies have demonstrated that regression models may determine which parameters of an aneurysm contribute to rupture. In this study, the authors derived a modified binary logistic regression model and then validated it in a distinct cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…Most of studies emphasize that aneurysm size is a major risk for initial rupture [31] [32]. Lei-Mei Guo et al found that the probability of re-bleeding in patients with aneurysms larger than 10 mm was 1.624 fold greater than those with aneurysms of 10 mm or less [23], but this result is not consistent with other studies [22] [17].…”
Section: -Aneurysm Sizecontrasting
confidence: 51%
“…Most of studies emphasize that aneurysm size is a major risk for initial rupture [31] [32]. Lei-Mei Guo et al found that the probability of re-bleeding in patients with aneurysms larger than 10 mm was 1.624 fold greater than those with aneurysms of 10 mm or less [23], but this result is not consistent with other studies [22] [17].…”
Section: -Aneurysm Sizecontrasting
confidence: 51%
“…It is also encouraging that these data reflect blinded technologists' measurements off of 2-dimensional angiographic images obtained at the time of presentation suggesting that there is an ease of real-world applicability with SR, which has been a criticism of other more complicated morphometrics. 15 It should be noted that various patient factors such as age and comorbidities have been shown to confer rupture risk. These factors were not found to be significantly different between the unruptured and ruptured groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with previous studies on single aneurysms. [14][15][16][17][18]22 The current objective is to evaluate the mutual influence between aneurysm sacs. (More specifically, to evaluate the hemodynamic factor's variation in aneurysm a 2 caused by changing the geometrical characteristics of a 1 .)…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Since hemodynamics, which strongly depend on the vascular geometry, play a key role in aneurysm growth and rupture, the geometrical characteristics seem to be an important factor in predicting rupture risk. The influences of aneurysm geometry characteristics on the rupture of single aneurysms have been discussed in the literature, including aneurysm size, [14][15][16][17][18] shape, [19][20][21] size ratio (SR) (height/ width), 22 section size, 21 and inflow angle. 23 However, few articles have analyzed the reasons for the higher rupture rate of multiple aneurysms.…”
Section: Introductionmentioning
confidence: 99%